Constitutional culture in the Belarusian society - Sharo, Otto U. (Journal of the Belarusian State University. Law, 2026)
Human rights and freedoms are the most valuable priorities for the constitutional order of the Republic of Belarus. There is a point of view that life generates law, but reality itself cannot be integrated into a specific legal norm due to its diversity and completeness. When processes occur in society that require subsequent ordering, legal regulation arises. In general, this situation can appear, but speaking of constitutional culture, the process is designed to be the opposite. Human behaviour must obey the constitutional requirement, in this sense, reality is designed to copy constitutional law, to create through it a familiar environment of social structure. The article examines the phenomenon of constitutional culture in the Belarusian society in the historical period since the end of the 20th century up to modern times. It studies on the basis of a comprehensive analysis approaches to understanding of this phenomenon, the legal positions of constitutional scholars, the circumstances of reality influencing the formation and rooting of constitutional culture. It is concluded that constitutional culture is intended to become part of the national cultural code.